2021
DOI: 10.1037/ort0000555
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable yet forgotten? A systematic review identifying the lack of evidence for effective suicide interventions for young people in contact with child protection systems.

Abstract: Children and young people in out-of-home care are at a higher risk of suicide than young people not involved with child protection systems. Despite this, there is a lack of evidence of effective suicide prevention interventions for this vulnerable population. We reviewed the types of suicide prevention interventions that have been used and evaluated with children and young people and staff and carers in out-of-home care/child protection systems. We conducted a systematic review of existing literature using PRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Conversely, there was a dearth of interventions targeting subjective wellbeing and suicide-related outcomes, despite care-experienced young people reporting relative adversity in these areas compared to the general population [ 7 , 8 ]. This reflects wider findings in the research evidence, with a recent review of suicide prevention interventions for children involved in child protection services also identifying a paucity of evidence-based approaches [ 192 ]. New interventions might be developed to target these outcomes, or existing approaches adapted if theoretically appropriate.…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, there was a dearth of interventions targeting subjective wellbeing and suicide-related outcomes, despite care-experienced young people reporting relative adversity in these areas compared to the general population [ 7 , 8 ]. This reflects wider findings in the research evidence, with a recent review of suicide prevention interventions for children involved in child protection services also identifying a paucity of evidence-based approaches [ 192 ]. New interventions might be developed to target these outcomes, or existing approaches adapted if theoretically appropriate.…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that intervention in childhood to forestall the development of ideation might reduce risks for longer-term ideation, attempts, and death by suicide. Unfortunately, a recent systematic review of interventions across the globe found that only two evidence-based interventions reduced SI in youth in foster care, and both were focused on adolescents (Russell et al, 2021).…”
Section: The Need For Early Preventive Interventionsmentioning
confidence: 99%
“…Importantly, neither of those two programs targeted SI directly (Russell et al, 2021). Instead, they focused on building positive skills in the youths and/or their caregivers.…”
Section: The Need For Early Preventive Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we do not yet have an evidence-based, validated set of clinical treatment guidelines for treating pediatric self-harm [ 21 ]. Despite a growing number of encouraging treatment studies in recent years, systematic reviews and meta-analyses conclude that replication of positive effects from dialectical behaviour therapy (DBT) is needed and that more clinical trial research is still required for mentalization and family-based therapies to determine efficacy [ 22 – 24 ] Moreover, gaps in this corpus of work include an absence of studies about treatments for self-harm in children younger than 12 years and a paucity of trials for particularly vulnerable sub-groups such as those in care [ 25 ] and non-cis-gender children or adolescents [ 24 ]. No randomized controlled trials (RCTs) of pharmacological interventions for pediatric self-harm have been published and the results from non-RCT studies using adaptations of adult medication treatments have been disappointing [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%